2019
DOI: 10.1111/tran.12287
|View full text |Cite
|
Sign up to set email alerts
|

Commoning mobility: Towards a new politics of mobility transitions

Abstract: Scholars have argued that transitions to more sustainable and just mobilities require moving beyond technocentrism to rethink the very meaning of mobility in cities, communities, and societies. This paper demonstrates that such rethinking is inherently political. In particular, we focus on recent theorisations of commoning practices that have gained traction in geographic literatures. Drawing on our global comparative research of low‐carbon mobility transitions, we argue that critical mobilities scholars can r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(71 citation statements)
references
References 70 publications
0
57
0
7
Order By: Relevance
“…Research reviewing different perspectives on mobility justice (e.g Pereira et al, 2016;Sheller, 2018;Lucas et al, 2015) shows how particular roots/routes for understanding justice imply quite different approaches and interventions into mobility. How mobility is understoodwhether as migration or transport, a resource, an amalgam of movement, practice and meaning (Cresswell, 2010b) a commons (Nikolaeva et al, 2019), an enfolding life-path (King, 2012) -or as I have suggested herea transformation of material-semiotic energy, will also have implications for how mobility justice is imagined.…”
Section: Mobility Justicementioning
confidence: 99%
See 1 more Smart Citation
“…Research reviewing different perspectives on mobility justice (e.g Pereira et al, 2016;Sheller, 2018;Lucas et al, 2015) shows how particular roots/routes for understanding justice imply quite different approaches and interventions into mobility. How mobility is understoodwhether as migration or transport, a resource, an amalgam of movement, practice and meaning (Cresswell, 2010b) a commons (Nikolaeva et al, 2019), an enfolding life-path (King, 2012) -or as I have suggested herea transformation of material-semiotic energy, will also have implications for how mobility justice is imagined.…”
Section: Mobility Justicementioning
confidence: 99%
“…Discourses of scarcity (e.g. lack of funding, road space and the need to curb emissions) mean government-led initiatives are cut, and responsibility for mobility is shifted to individual, privatised or community-level responsibility (Nikolaeva et al, 2019).…”
mentioning
confidence: 99%
“…Also, following Aldred (2010), and in resonance with the rhetoric of community A. Nikolaeva, et al Journal of Transport Geography 79 (2019) 102486 and commons in cycling innovation texts (see the examination of Ring-Ring application in Nikolaeva et al, 2019) we would refrain from interpreting particular expressions of care for the self and the environment as exclusively neoliberal. Thus, further research is needed to explore the politics of cycling and its relationship to wider changes in urban governance, including neoliberalisation.…”
Section: Smart Cycling Citizensmentioning
confidence: 99%
“…Geographers publish a lot on the politics of mobility (for example, see Nikolaeva et al., ). Here, we want to add to that corpus; augment those limited numbers of studies that reflect on what connects walking, streets, and democracy; and link these issues to others framed by pragmatic philosopher John Dewey (1859–1952).…”
Section: Introductionmentioning
confidence: 99%